2013
DOI: 10.1680/adcr.12.00032
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of radionuclides in the presence of superplasticiser

Abstract: Superplasticisers improve the flow properties of fresh cement and offer undoubted benefits to the construction sector. There is concern in the nuclear industry, however, that the presence of a superplasticiser in grout or backfill cement may increase the solubility of radionuclides in the cementitious pore water and/or reduce their adsorption from solution. This paper describes the effect of a commercial, polycarboxylated, polyether comb type superplasticiser on the behaviour of selected metals in blended ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Although there are clear operational benefits to be gained from using SPs, it is important from a safety case perspective to understand their effect on the longterm behaviour of the encapsulated radioactive inventory. Research has shown that these high-molecular-weight, watermiscible, organic polymers have the potential to both enhance radionuclide solubility (McCrohon and Williams, 1997) and inhibit the uptake and incorporation of radionuclides by the cement matrix (Young et al, 2013). Further, it has been shown that proprietary SPs vary substantially in their complexation behaviour depending on the cement and experimental conditions (Young et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are clear operational benefits to be gained from using SPs, it is important from a safety case perspective to understand their effect on the longterm behaviour of the encapsulated radioactive inventory. Research has shown that these high-molecular-weight, watermiscible, organic polymers have the potential to both enhance radionuclide solubility (McCrohon and Williams, 1997) and inhibit the uptake and incorporation of radionuclides by the cement matrix (Young et al, 2013). Further, it has been shown that proprietary SPs vary substantially in their complexation behaviour depending on the cement and experimental conditions (Young et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that these high-molecular-weight, watermiscible, organic polymers have the potential to both enhance radionuclide solubility (McCrohon and Williams, 1997) and inhibit the uptake and incorporation of radionuclides by the cement matrix (Young et al, 2013). Further, it has been shown that proprietary SPs vary substantially in their complexation behaviour depending on the cement and experimental conditions (Young et al, 2013). Commercial SP formulations may also contain a number of adjuncts, including de-foaming agents, biocides, viscosity modifiers and other impurities, all of which may affect cement pore solution chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They show that the use of cement replacement materials can improve resistance to chloride ingress. However, they caution that carbonation may release bound chlorides, so that whilst measurement of free chlorides is usually employed as a ready way of testing for corrosion potential of reinforced concrete structures, the bound chloride content should not be overlooked.Taking durability performance to an extreme, Young et al (2013) consider the application of cementitious materials for the encapsulation of radionuclides. They have investigated the sorption behaviour of a range of radionuclides onto ggbs-and pfa-bearing grouts in the presence of superplasticisers.…”
mentioning
confidence: 99%
“…Taking durability performance to an extreme, Young et al (2013) consider the application of cementitious materials for the encapsulation of radionuclides. They have investigated the sorption behaviour of a range of radionuclides onto ggbs-and pfa-bearing grouts in the presence of superplasticisers.…”
mentioning
confidence: 99%